A Soft-Switched DC/DC Converter Using Integrated Dual Half-Bridge with High Voltage Gain and Low Voltage Stress for DC Microgrid Applications - Hadi Moradisizkoohi (Inventions, 2018)
In this paper, a soft-switched boost converter including an integrated dual half-bridge circuit with high voltage gain and continuous input current is introduced that can be suitable for the applications requiring a wide voltage gain range, such as for the front-end of the inverter in a DC microgrid to integrate renewable energy sources (RES). In the proposed converter, two half-bridge converters are connected in series at the output stage to enhance the voltage gain. Additionally, the balanced voltage multiplier stage is employed at the output to increase the voltage conversion ratio, as well as distribute the voltage stress across semiconductors; hence, switches with smaller on-resistance RDS(on) can be adopted resulting in an improvement in the efficiency. The converter takes advantage of the clamp circuit not only to confine the voltage stress of switches, but also to achieve the soft-switching, which leads to a reduction in the switching loss as well as the cost. The mentioned features make the proposed converter a proper choice for interfacing RES to the DC-link bus of the inverter. The operation modes, steady-state analysis, and design consideration of the proposed topology have been demonstrated in the paper. A 1-kW laboratory prototype was built using gallium nitride (GaN) transistors and silicon carbide (SiC) diodes to confirm the effectiveness of the proposed topology.